(Invited) Modeling Morphology Distribution in Injection Molded Polypropylene Parts. (13th December 2018) - Pantani, Roberto; Liparoti, Sara; Speranza, Vito; Titomanlio, Giuseppe
Abstract : The morphology distribution in the final molded object is determined by temperature, pressure and flow, experienced during the process, and their effects on relaxation times, nucleation density, spherulitic growth rate, and the interrelation among these quantities with the deformation rate. The combination of the models developed to describe all these effects becomes a model for predicting the morphology evolution during the injection molding process. This model was implemented in the UNISA code. In this work, samples obtained with a fast evolution of cavity surface temperatures were analyzed and the results were compared with the UNISA code simulations. The fibrillar layer morphology was related to the achievement of critical values of both the molecular stretch and the mechanical work, the latter being performed after the achievement of the critical molecular stretch. The dependence of the morphological layers thicknesses upon the heating conditions was satisfactorily described by the model.